Role of acquired immunity and natural age resistance on course of Isospora suis coccidiosis in nursing piglets - Koudela, B; Kucerová, S (Veterinary parasitology, 1999)
Thirty-two piglets from three litters were experimentally inoculated with 200000 sporulated oocysts of Isospora suis at 3 days of age and/or rechallenged at 19 days of age or primary inoculated at 19 days of age, to compare the role of acquired immunity and natural age resistance on the course of coccidiosis. Twelve piglets were not inoculated and served as a control. Following challenge, the signs of coccidiosis characterised by clinical symptoms, oocysts shedding and weekly weights were similar to those which occurred in piglets primary inoculated at 19 days of age. This comparison suggests that maturation of non-specific components of the immune system plays a more important role in the resistance of neonatal piglets to I. suis infection than specific immune mechanisms.
Keywords: prasata; imunita získaná od matky; počet parazitárních vajíček; Feces; Swine; Aging; kokcidióza; porodní hmotnost; Parasite Egg Count; Pregnancy; těhotenství; Immunity, Maternally-Acquired; Coccidiosis; Body Weight; Animals, Suckling; Animals; ženské pohlaví; Birth Weight; nemoci prasat; zvířata; stárnutí; průjem; kojená zvířata; Isospora; Swine Diseases; Diarrhea; Female; feces; tělesná hmotnost